How goats avoid ingesting noxious insects while feeding. Issue 1 (December 2017) - Berman, Tali; Ben-Ari, Matan; Glasser, Tzach; Gish, Moshe; Inbar, Moshe
Abstract As mammalian herbivores feed, they often encounter noxious insects on plants. It is unknown how they handle such insects. We experimentally examined the behavioural responses of goats to the noxious spring-webworm (Ocnogyna loewii ), and manipulated their sensory perception to reveal the process of insect detection. Goats did not avoid plants with webworms, demonstrating a remarkable ability to sort them apart from the plant (98% of webworms survived). Initial detection of webworms involved tactile stimulation, done by repeatedly touching the leaves with the muzzle. This enabled them to pick webworm-free leaves. If the goats picked up leaves with a webworm, they shook or discarded the leaf. They spat out webworms that entered their mouths, after detecting them by touch and taste. By using their keen senses and efficient behaviours, goats are able to feed while accurately excluding insects. These findings highlight the importance of direct interactions between mammalian herbivores and insects.